Performance evaluation of a fast handoff scheme for CAPWAP Centralized WLAN - Balfaqih, Mohammed Abobakr Ahmed (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The growing demand to provide secure wireless connectivity, especially in hot spot areas such as conference halls and events, introduced centralized Wireless Local Area Network (WLAN). The centralized WLAN utilizes Access Controller (AC) to simplify configuration, management and control of Wireless Termination Points (WTPs) in a large-scale deployment of wireless network. To manage the connection between these two entities, Control and Provisioning of Wireless Access Point (CAPWAP) Working Group has defined standard interoperable protocol. Currently, deployment of a CAPWAP centralized WLAN poses a challenge for real-time applications that are sensitive to network latencies such as gaming, audio and Voice over Internet Protocol (VoIP). In order to roam the mobile clients between the WTPs, scanning and authentication phases are performed, which are considered as the main handoff latency components. This excessive latency in turn will cause disruption on the ongoing session, which is unsuitable for real-time applications. The scanning phase produces highest latency with more than 90% of the total handoff latency in CAPWAP centralized WLAN (Behcet S., 2006). This dissertation aims to propose a fast handoff scheme for CAPWAP Centralized WLAN by determining the next WTP before initiating the MAC layer handoff process. The setup phase latency of network entities and the handoff process in CAPWAP centralized WLAN are, firstly, evaluated using CAPWAP centralized WLAN simulator developed by Visual Basic.NET (VB.NET). This is to evaluate the association latency of the CAPWAP protocol to ensure that the CAPWAP can effectively be used in network management and validate the developed simulator. Then, the proposed scheme is evaluated and benchmarked with the standard Active Scan Method (IEEE Std. 802.11, 2012) and Fast Handoff Mechanism in WLANs Based on Neighbor Graph Information (Sarddar D., 2010). The obtained results show that pre-configuring the IP address of the AC in the WTPs could bring down the setup latency to 84ms, regardless of the number of WTPs per AC. The case of the setup process with considering failure states showed that error during negotiation, in the worst case scenario, increases the setup latency by almost 12 times. On the other hand, during the handoff process, the results show that the scanning latency is the main contributor of the handoff latency. The scanning latency represents around 87% (in active scan) and around 96% (in passive scan) of the total handoff latency. Moreover, the results show that the proposed Fast Handoff scheme reduces 85.5% of the handoff latency using active scan method. The handoff latency is around 41.12 ms compared to 134.63 ms using the benchmark work. The signaling cost is also decreased using the proposed scheme to around 87.26% compared to the active scan method.